Unique molecular signatures influencing the biological function and fate of post‐natal stem cells isolated from different sources. (10th December 2012) - Abu Kasim, Noor Hayaty; Govindasamy, Vijayendran; Gnanasegaran, Nareshwaran; Musa, Sabri; Pradeep, Padmaja Jayaprasad; Srijaya, Thekkeparambil Chandrabose; Aziz, Zeti Adura Che Ab.
Abstract: The discovery of mesenchymal stem cells (MSCs) from a myriad of tissues has triggered the initiative of establishing tailor‐made stem cells for disease‐specific therapy. Nevertheless, lack of understanding on the inherent differential propensities of these cells may restrict their clinical outcome. Therefore, a comprehensive study was done to compare the proliferation, differentiation, expression of cell surface markers and gene profiling of stem cells isolated from different sources, viz. bone marrow, Wharton's jelly, adipose tissue and dental pulp. We found that although all MSCs were phenotypically similar to each other, Wharton's jelly (WJ) MSCs and dental pulp stem cells (DPSCs) were highly proliferative as compared to bone marrow (BM) MSCs and adipose tissue (AD) MSCs. Moreover, indistinguishable cell surface characteristics and differentiation capacity were confirmed to be similar among all cell types. Based on gene expression profiling, we postulate that BM‐MSCs constitutively expressed genes related to inflammation and immunodulation, whereas genes implicated in tissue development were highly expressed in AD‐MSCs. Furthermore, the transcriptome profiling of WJ‐MSCs and DPSCs revealed an inherent bias towards the neuro‐ectoderm lineage. Based on our findings, we believe that there is no unique master mesenchymal stem cell that is appropriate to treat all target diseases. More precisely, MSCs from different sources exhibit distinct and unique gene expression signatures that make them competent to give rise to specific lineages rather than others. Therefore, stem cells should be subjected to rigorous characterization and utmost vigilance needs to be adopted in order to choose the best cellular source for a particular disease. Copyright © 2012 John Wiley & Sons, Ltd.